2018
DOI: 10.1108/ijse-11-2016-0303
|View full text |Cite
|
Sign up to set email alerts
|

Financial literacy among youth

Abstract: Purpose The purpose of this paper is to analyse the level of financial literacy among youth in the world based on previous studies. The study, particularly, focus at how socio-economic and demographic factors such as age, gender, marital status and income influence financial literacy level of youth and whether there is any interrelationship between financial knowledge, financial attitude and financial behaviour. Strong endeavour of the world economies to improve the financial well-being of their citizens has c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
133
2
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(244 citation statements)
references
References 48 publications
16
133
2
20
Order By: Relevance
“…The current research findings show that appropriate financial attitude and financial knowledge are critical for achieving better levels in individuals' financial behaviour even in the context of a post-communist transition country like Albania. These findings are consistent with prior research (Fessler et al, 2019;Garg & Singh, 2018;Potrich et al, 2016). The present finding is a further addition to the existing literature.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The current research findings show that appropriate financial attitude and financial knowledge are critical for achieving better levels in individuals' financial behaviour even in the context of a post-communist transition country like Albania. These findings are consistent with prior research (Fessler et al, 2019;Garg & Singh, 2018;Potrich et al, 2016). The present finding is a further addition to the existing literature.…”
Section: Discussionsupporting
confidence: 93%
“…A report from OECD (2013) defines financial literacy as a mixture of skill, behaviour, awareness, attitude, and knowledge, which are essential for sound financial decisions making for an individual to achieve the state of financial well-being. Many scholars and experts stated that financial literacy is inclusive of the three components: financial attitude, financial knowledge, and financial behaviour (Atkinson & Messy, 2012;Garg & Singh, 2018;Huston, 2010;Potrich et al, 2015;Santini et al, 2019). Thus, the above expositions expressed that financial literacy covered three broad concepts: financial attitude, financial knowledge, and financial behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…Hogarth and Hilgert, (2002) underline that middle age groups tend to have high financial literacy compared to young or old age groups. However, this research is different with Mouna and Anis (2017) and Garg and Singh (2018). They found that the financial literacy was affected by age, education level, and the annual income.…”
Section: Resultsmentioning
confidence: 65%
“…Financial attitudes will be able to help financial behavior, including financial management, financial budgeting and decision making, therefore attitudes towards finance in this study will be able to influence financial behavior if the millennial generation has an attitude towards the rest of the money, attitudes toward budget and frugality. Financial behavior has been carried out by many financial researchers, especially behavioral financial management [7], [8], [9], [10], [11], as has also been linked to financial management behaviors associated with generations of differences [12 ], [13], [14], [15], [16], [17], however, research in the Indonesian context, which is associated with the behavior of the financial management of the millennial generation, has not been widely implemented. Therefore this paper tries to reveal the antecedents of millennial generation financial management behavior with two important variables, namely financial knowledge and attitudes towards finance.…”
Section: Introductionmentioning
confidence: 99%